2018
DOI: 10.1103/physrevlett.121.127704
|View full text |Cite
|
Sign up to set email alerts
|

Interaction-Driven Giant Orbital Magnetic Moments in Carbon Nanotubes

Abstract: Carbon nanotubes continue to be model systems for studies of confinement and interactions. This is particularly true in the case of so-called "ultra-clean" carbon nanotube devices offering the study of quantum dots with extremely low disorder. The quality of such systems, however, has increasingly revealed glaring discrepancies between experiment and theory. Here we address the outstanding anomaly of exceptionally large orbital magnetic moments in carbon nanotube quantum dots. We perform low temperature magnet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Unlike the hydrogen atom, whose ground-state has an orbital magnetic moment of zero (m = 0) due to spherical symmetry, in the case of a dot formed in a 2D material there is a finite out-of-plane orbital magnetic moment even for the s-shell, as a result of the reduced dimension along the z-axis. The orbital magnetic moment of a moving charge in a circular orbit, is given by [35,36]: µ orb = rev F /2, where r is the radius of the orbital, v F the Fermi velocity and e the charge of the electron. Assuming a Fermi velocity around 1 × 10 5 m/s, we obtain a radius for the P1, P2 and P3 resonances of 2±1, 9±2 and 6±1 nm, in relatively good agreement with the estimations of the dot size based on the capacitance extracted from the addition energies ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the hydrogen atom, whose ground-state has an orbital magnetic moment of zero (m = 0) due to spherical symmetry, in the case of a dot formed in a 2D material there is a finite out-of-plane orbital magnetic moment even for the s-shell, as a result of the reduced dimension along the z-axis. The orbital magnetic moment of a moving charge in a circular orbit, is given by [35,36]: µ orb = rev F /2, where r is the radius of the orbital, v F the Fermi velocity and e the charge of the electron. Assuming a Fermi velocity around 1 × 10 5 m/s, we obtain a radius for the P1, P2 and P3 resonances of 2±1, 9±2 and 6±1 nm, in relatively good agreement with the estimations of the dot size based on the capacitance extracted from the addition energies ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The observed behavior in our devices could also be described using the simple model of a uniform electron gas with exchange interaction (presented in the Supplemental Material). However, given the overwhelming evidence for Wigner crystallization from other experiments [16][17][18][19] in the parameter space of our devices, we can safely suggest our observed compressibility behavior as a probe of interaction strength of 1D Wigner crystals. Future studies will incorporate independent control of bandgap and confining potential.…”
mentioning
confidence: 51%
“…As a clean, interacting quantum system, electrons in a suspended CNT at low density [14] may be described as a Wigner crystal [15]. Indeed, experimental studies have confirmed fascinating magnetic and electronic properties of the Wigner crystal phase, such as their exponentially suppressed exchange energy [16], absence of excited energy states [17] and giant orbital magnetic moment [18]. These observations indicate that despite more than a decade of studies on the 1D Wigner crystal, improvement in device fabrication and higher quality carbon nanotubes lead to the discovery of novel signatures that have not been revealed before.…”
mentioning
confidence: 99%
“…The elementary excitations of the liquid are plasmons, whose velocities depend on the residual, shortrange interaction. 12 Undoped NTs are always insulating, 3,4,19,26,39,40 including the armchair kind, which band theory predicts to be metallic and protected against gap-opening perturbations. 2 The contribution to the gap that is not accounted for by independentelectron models is thought to have a many-body origin, whose features-again-critically depend on the range of electronelectron interaction.…”
Section: Introductionmentioning
confidence: 99%